2013
DOI: 10.2196/jmir.2413
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adolescent Asthma Symptoms and Adherence Using Mobile Phones

Abstract: BackgroundSelf-report is the most common method of measuring medication adherence but is influenced by recall error and response bias, and it typically does not provide insight into the causes of poor adherence. Ecological momentary assessment (EMA) of health behaviors using mobile phones offers a promising alternative to assessing adherence and collecting related data that can be clinically useful for adherence problem solving.ObjectiveTo determine the feasibility of using EMA via mobile phones to assess adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 20 publications
0
69
0
1
Order By: Relevance
“…Mulvaney et al previously demonstrated that EMAs focused on asthma are associated with established measures of asthma control (e.g., Asthma Control Test) but also noted the difficulty in obtaining patient self-reported medication use. [20] Our study adds to this research by using newer technology for passive collection of medication use data, BT inhaler devices, and demonstrating an association of contextual factors such as asthma symptoms and emotional state by EMA with the adherence device data. Calculated adherence over days, weeks, months, and years is a series of discrete events occurring in a patient's daily life that can be impacted by mood and motivation.…”
Section: Limitationsmentioning
confidence: 76%
See 3 more Smart Citations
“…Mulvaney et al previously demonstrated that EMAs focused on asthma are associated with established measures of asthma control (e.g., Asthma Control Test) but also noted the difficulty in obtaining patient self-reported medication use. [20] Our study adds to this research by using newer technology for passive collection of medication use data, BT inhaler devices, and demonstrating an association of contextual factors such as asthma symptoms and emotional state by EMA with the adherence device data. Calculated adherence over days, weeks, months, and years is a series of discrete events occurring in a patient's daily life that can be impacted by mood and motivation.…”
Section: Limitationsmentioning
confidence: 76%
“…We cannot confirm the presence or absence of asthma symptoms reported with EMA, but previous studies suggest this approach is valid in multiple disease states including asthma. [19,20,23] Furthermore, individual participants may experience symptoms differently due to different body awareness and this could impact their symptom reporting and particularly their severity of reported symptoms. More so, as a pilot study, we permitted the youth and parent to decide if the child was to report symptoms alone or in collaboration with the parent.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12,13 Over the past two years, the number of medication adherence apps available on the market significantly increased from 160 to 461. 14,15 This remarkable increase confirms the rising demand of medication adherence apps, which can be used by nearly all patient populations.…”
Section: Emergence Of Medication Adherence Mobile Appsmentioning
confidence: 99%